Association study of a dopamine transporter polymorphism and attention deficit hyperactivity disorder in UK and Turkish samples - (:unkn) unknown (NATURE PUBLISHING GROUP, 2001)
Molecular genetic studies in attention deficit hyperactivity disorder (ADHD) have focussed on candidate genes within the dopamine system, which is thought to be the main site of action of stimulant drugs, the primary pharmacological treatment of the disorder.(1) Of particular interest are findings with the dopamine transporter gene (DAT1), since stimulant drugs interact directly with the transporter protein.(2,3) To date, there have been eight published association studies of ADHD with a 480 base-pair allele of a variable number tandem repeat (VNTR) polymorphism in the 3'-untranslated region of the gene, five(4-8) that support an association and three(9-11) against. We have analysed the same VNTR marker in a dataset of UK Caucasian children and an independent dataset of Turkish Caucasian children with DSM-IV ADHD, using the transmission disequilibrium test (TDT).(12) Results from the UK (chi (2) = 8.97, P = 0.001, OR = 1.95), but not the Turkish sample (chi (2) = 0.93, P = 0.34) support association and linkage between genetic variation at the DAT1 locus and ADHD. When considered alongside evidence from other published reports, there is only modest evidence for the association, consistent with a very small main effect for the 480-bp allele (chi (2) = 3.45, P = 0.06, OR = 1.15), however we find significant evidence of heterogeneity between the combined dataset (chi (2) = 22.64, df = 8, P = 0.004).
Keywords: dopamine transporter; DAT1; ADHD; genetic association; LINKAGE DISEQUILIBRIUM; CHILDREN; GENE; METHYLPHENIDATE; TRANSMISSION; RELIABILITY; COCAINE; DAT1; DRD5; ADHD